Development of Assessment Tool in Measuring the Parenting Style of Teachers as Second Parents - Villafuerte, Ma. Shayne Rose (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and preliminarily validated the Teacher Parenting Style Assessment Tool, an instrument designed to measure teachers’ parenting-like behaviors as second parents in academic settings. Grounded in Baumrind’s Parenting Style Theory and supported by Bronfenbrenner’s Ecological Systems Theory, Bandura’s Social Learning Theory, and Attachment Theory, the study operationalized teachers’ caregiving, disciplinary, instructional, emotional, and psychosocial roles into measurable behavioral domains. A sequential, deductive mixed-methods design was used. The first phase involved a PRISMA-guided systematic literature review of 99 eligible studies to identify behavioral indicators. The second phase translated these indicators into domains, subdomains, and Likert-scale items. The third phase involved content validation by six experts, face validation by six in-service teachers, cognitive pretesting with another six teachers, and pilot testing among 50 in-service teachers from elementary, secondary, and tertiary levels in Camarines Sur. Findings identified six major behavioral dimensions: behavioral regulation and anti-bullying practices, academic self-regulation support, developmentally responsive care, discipline and behavioral adjustment, instructional control and responsiveness, and emotional and psychosocial support. The instrument showed strong preliminary validity, with 44 items retained after content validation, strong face validity, and cognitive revisions for clarity. Reliability testing yielded a Cronbach’s alpha of 0.88 and split-half reliability of 0.96, resulting in a refined 31-item tool. The study supports SDG 4 on Quality Education, SDG 3 on Good Health and Well-Being, SDG 16 on safe and inclusive learning environments, and SDG 17 on collaborative learner support. Its sustainability impact lies in strengthening educational, psychosocial, institutional, and developmental support systems through reflective and evidence-based teacher assessment.